Implementation of Electronic Government through the Application of Efficiency of Land and Building Tax Online Services at the Regional Revenue Agency Office - Cahya Aini, Nadia; Imaniar, Dimas; Wahyudiono, Andhika (Green Publisher Indonesia, 2024)
Background: The use of information technology through E-Government has become an interesting topic, one of which is realized with the UN E-Counter Application which was developed due to complaints from the public about the long distance from the location of the UN service application which can only be done at MPP and PPP. Purpose: The purpose of this study is to describe, analyze and explain the application of E-Government through the UN E-Counter application at the office of the Regional Revenue Agency of Banyuwangi Regency. Method: The research method used is descriptive research with a qualitative approach. This approach was chosen because it aims to know and describe the application of electronic government through the application of the efficiency of the Land and Building Tax online service at the Office of the Regional Revenue Agency of Banyuwangi Regency. The UN E-Counter application is in accordance with the principles of implementing E-Government. Results: The results show that the principle of implementing E-Government in the UN E-Counter Application has been applied quite well, but it still needs improvement in the development of the application so that it can be used directly by the community without going through the intermediary of Village or Village devices Conclusion: The conclusion of this study shows that the application of E-Government through the UN E-Counter Application is in accordance with the principles of implementing E-Government according to Indrajit which consists of 6 components, namely the Benefits of E-Government, Success Factors for the implementation of E-Government, E-Government Challenges, Types of E-Government Services, Types of E-Government Relations, and Principles of E-Government Implementation